US-Pakistan Relations: Examining Challenges to Sovereignty from 2008 to 2022 - Khan, Aneel Waqas; Irfan, Adeel; Khurshid, Kiran (Annals of Human and Social Sciences, 2023)
This research empirically investigates the multifaceted challenges to sovereignty within the framework of US-Pakistan relations from 2008 to 2022. The objective of the article is to explore US interventions subjugate the Paksitan’s sovereignty. Experts shows concern, arguing that the ties between the US and Pakistan have been topsy-turvy. Pakistani state faced challenges to sovereignty on various occasions before 9/11. The study employs a qualitative research method to analyze scholarly literature, and policy documents along with reports published by international organizations like the UN and national organization like IPRI, etc. The research sheds light on the complexities of this bilateral relationship, examining sovereignty issues such as political tensions, and diplomatic dilemmas. It highlights the violations in the fields of territorial sovereignty, civilian casualties and public outrage, and political and diplomatic crisis. The findings offer a comprehensive understanding of the intervention made by the US during this specific era to influence the Pakistan’s sovereignty in the form of drone strikes, use of air bases, assassination of Al Qaeda leader Osama Bin Laden, etc. Pakistan and US must step towards the bilateral relationship and collaborate at social, cultural, economic and political level for the progress and prosperity of the region.